Evaluation of Coagulation Profile in T2DM Patients On Metformin: A Cross-Sectional Study - Vyshnavi Shanbagh; Narendranath S; Renuka B G; Dr. Sushma H K; Vijayalakshmi Malya; Shashikala G H (International Journal of Pharma and Bio Sciences, 2024)
The incidence of cardiovascular disease due to thrombosis is 2-4 folds greater in diabetic patients with diabetes. Prothrombin time, activated partial thromboplastin time, and platelet count are hematological indices that give an insight into the coagulation status. Decreased/deficient vitamin B12 levels are now considered a common side effect in patients on metformin treatment, especially in those receiving a higher dose or longer treatment duration, which leads to an increase in homocysteine and hyperhomocysteinemia levels are linked to thrombosis. Hence, this study aimed to assess the coagulation status of patients with type 2 diabetes on a higher dose of metformin and to compare it with that of patients with type 2 diabetes mellitus receiving a lower dose of metformin. A comparative cross-sectional study was conducted at Bapuji Hospital and Chigateri Government Hospital, attached to the JJM Medical College, Davangere. A total of 50 treated type II diabetes treated with metformin (>1500 mg/day and <1500 mg/day) were included. After obtaining informed consent, a structured questionnaire was used to collect the sociodemographic data. Following the interview, 4 ml of blood was collected to determine the two groups' PT(Prothrombin time), aPTT(activated partial thromboplastin time,) and INR (international normalized ratio )values. The data were analyzed using SPSS version 20. An unpaired "t" test was used to compare the mean PT, aPTT, and INR counts among the groups. A P significance was set at P < 0.05. The mean aPTT and PT of T2DM patients (>1500mf/day metformin) had a mean aPTT, PT, and INR of 26.97 ± 5.25, 11.93 ± 1.06, and 1.024 ± 0.1 and T2DM (< 1500 mg/day metformin) had mean aPTT, PT, and INR of 31.76 ± 6.25, 13.08 ± 1.36, and 1.148 ± 0.12, respectively. The odds ratio was 5.4, which revealed that the aPTT values were 5.4 times more in controls than in cases. There was a significant shortening of aPTT, PT, and INR in cases compared with controls (P < 0.05). Shortening of aPTT, PT, and INR in T2DM may be a useful marker. Therefore, monitoring aPTT and PT in T2DM patients receiving a higher metformin dose is important to prevent hypercoagulation.